Diagonal direct limits of finite symmetric and alternating groups - Lavrenyuk, Y.V.; Nekrashevych, V.V.; Sushchansky, V.I. (Algebra and Discrete Mathematics, 2010)
Diagonal direct limits of permutation groups are studied using their representations by homeomorphisms of the boundary of rooted trees.